MATHMART: Media Pembelajaran Matematika Digital Bermodel PBL Berpendekatan STEM untuk Pemenuhan Tuntutan Pendidikan Abad 21 - Amalia, Eka Nurul; Ainurrokhimah, Awwalina; Saputra, Zacky Akhlis; Fakhriyana, Dina (Jurnal Tadris Matematika, 2024)
The 21st century demands that education implement student-centered learning, involve technology, and present learning that stimulates 4C abilities (critical thinking, creative thinking, collaboration, and communication). However, mathematics learning in formal education has not been able to meet the existing demands. Many the mathematics learning in formal education has not honed students' 4C abilities. As a solution, researchers took the initiative to develop MATHMART learning media that contain the material of the Two-Variable Linear Equation System (SPLDV) for grade VIII SMP/MTs students. Unlike other learning media, MATHMART has integrated the STEM approach and the Problem-Based Learning (PBL) model in its development. The type of research is Research and Development with the 4D model (Define, Design, Develop, Disseminate). The results of this study are an average percentage of validation at the development stage by media experts of 80.5% and material experts of 86%, both of which are categorized as very valid with slight revisions. After the revision, a practicality test was conducted on 22 students at Mifathussa'adah Middle School in Kudus, and an average percentage of the practicality questionnaire was 85%, with a convenient category. MATHMART learning media helps students better understand SPLDV material and develop students' 4C abilities. Thus, MATHMART learning media can be used to help educators and students in achieving the demands of the 21st century.